The Relationship Between Knowledge Of Complementary Foods Processing (MPASI) and Child Anthropometry - Bayu Irianti; Setiya Hartiningtiyaswati; Etin Rohmatin; Yati Budiarti; Melia Sinta (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2026)
Nutritional problems among infants and toddlers remain a major public health concern. Despite various interventions, child malnutrition persists, highlighting the influence of maternal, behavioral, and environmental factors. This study aimed to analyze the relationship between maternal knowledge of complementary food processing and child anthropometric status. A quantitative cross-sectional study was conducted among 75 mothers of children aged 6 months to 3 years selected from 10 Posyandu using simple random sampling. Maternal knowledge was assessed using a validated 25-item questionnaire. Child anthropometric status was measured using weight, height/length, mid-upper arm circumference, and body mass index according to the WHO Child Growth Standards. Data were analyzed using descriptive statistics and Fisher’s Exact Test. Most mothers had good knowledge of complementary food processing (61.3%), most children had normal nutritional status (90.7%). Maternal education was significantly associated with knowledge of complementary food processing (p = 0.014), whereas maternal age (p= 0.848), occupation (p= 1.000) were not. No significant association was found between maternal knowledge and child anthropometric status (p= 0.476). Maternal knowledge of complementary food processing was not significantly associated with child anthropometric status. Child nutritional outcomes are influenced by multiple factors beyond maternal knowledge, including feeding practices, socioeconomic conditions, health status, environmental factors.